Inventaires des quelques espèces de Caprelliens dans la zone de Mostaganem - BOURAS, Hanane (My University, 2018)
Caprelles or Caprellians are small amphipods crustaceans in the form of little known rods and not very studied in Algeria. In the Mostaganem’s cost, no studies have been done yet devoted to these small amphipods. The present work is part of an inventory of some Caprellian amphipods from the Mostaganem’s cost. We have sampled at three stations (Stidia, Salamandre and Sidi Mejdoub) by targeting two seaweeds Cystoseira stricta and Ulva lactuca using technical quadra . Through this study, we have identified 6 different species: Caprella danilevskii, Caprella andreae, Caprella liparotensis, Caprella hirsuta, Caprella grandimana and Caprella acanthifera. We noticed that C. danilevskii was only present in C. stricta. However, C. acanthifera was only found in U. lactuca of the Sidi Mejdoub station. In addition, the number of females in most species is larger than that the males, which may be due to predation by females because of their larger size than females. Added to this, some strange malformations have been noticed in the species Caprella danilevskii, Caprella hirsuta and Caprella grandimana of the Stidia station in the first segments of their anatomical structure. This could be due to the presence of toxic products that can come from various sources (Fisheries, agriculture, aquaculture ...).
Keywords: Caprelliens; Côte de Mostaganem; Inventaire; Caprellians; Crustaceans; Inventory